2004
DOI: 10.1128/iai.72.6.3344-3349.2004
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation and Complement-Dependent Inflammation byNeisseria meningitidisAre Independent of Lipopolysaccharide

Abstract: Fulminant meningococcal sepsis has been termed the prototypical lipopolysaccharide (LPS)-mediated gramnegative septic shock. Systemic inflammation by activated complement and cytokines is important in the pathogenesis of this disease. We investigated the involvement of meningococcal LPS in complement activation, complement-dependent inflammatory effects, and cytokine or chemokine production. Whole blood anticoagulated with lepirudin was stimulated with wild-type Neisseria meningitidis H44/76 (LPS ؉ ), LPS-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 49 publications
4
29
0
1
Order By: Relevance
“…We therefore measured the amount of LPS in each meconium sample and included only those with pictogram levels in the batch. Although these low amounts may induce some cytokine synthesis, amount in the range of micrograms is needed for LPS to induce complement activation (54). Thus, it can virtually be excluded that LPS 246 CASTELLHEIM ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore measured the amount of LPS in each meconium sample and included only those with pictogram levels in the batch. Although these low amounts may induce some cytokine synthesis, amount in the range of micrograms is needed for LPS to induce complement activation (54). Thus, it can virtually be excluded that LPS 246 CASTELLHEIM ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Each segment was closed end-to-end and formed small loops. The loops were rotated slowly in an incubator at 37°C for 3 h (22,23). After 3 h, plasma was separated, and proinflammatory cytokines and chemokines were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Although LPS is pivotal, other ligands on Gram-negative bacteria could also contribute to the pathogenesis of inflammation and sepsis. It is for instance shown that LPS-deficient N. meningitides (LPS -) can activate the complement system and induce complement mediated inflammatory effects (148). N. meningitides (LPS -) have also been shown to be able to induce large gene expression changes in human monocytes (149).…”
Section: Whole Live Escherichia Coli Bacteriamentioning
confidence: 99%